Structural and Photoluminescence Investigations of Tb(3+)/Eu(3+) Co-Doped Silicate Sol-Gel Glass-Ceramics Containing CaF(2) Nanocrystals - Pawlik, Natalia (Materials (Basel), 2021)
In this work, the series of Tb(3+)/Eu(3+) co-doped xerogels and derivative glass-ceramics containing CaF(2) nanocrystals were prepared and characterized. The in situ formation of fluoride crystals was verified by an X-ray diffraction technique (XRD) and transmission electron microscopy (TEM). The studies of the Tb(3+)/Eu(3+) energy transfer (ET) process were performed based on excitation and emission spectra along with luminescence decay analysis. According to emission spectra recorded under near-ultraviolet (NUV) excitation (351 nm, (7)F(6) → (5)L(9) transition of Tb(3+)), the mutual coexistence of the (5)D(4) → (7)F(J) (J = 6–3) (Tb(3+)) and the (5)D(0) → (7)F(J) (J = 0–4) (Eu(3+)) luminescence bands was clearly observed. The co-doping also resulted in gradual shortening of a lifetime from the (5)D(4) state of Tb(3+) ions, and the ET efficiencies were varied from η(ET) = 11.9% (Tb(3+):Eu(3+) = 1:0.5) to η(ET) = 22.9% (Tb(3+):Eu(3+) = 1:2) for xerogels, and from η(ET) = 25.7% (Tb(3+):Eu(3+) = 1:0.5) up to η(ET) = 67.4% (Tb(3+):Eu(3+) = 1:2) for glass-ceramics. Performed decay analysis from the (5)D(0) (Eu(3+)) and the (5)D(4) (Tb(3+)) state revealed a correlation with the change in Tb(3+)–Eu(3+) and Eu(3+)–Eu(3+) interionic distances resulting from both the variable Tb(3+):Eu(3+) molar ratio and their partial segregation in CaF(2) nanophase.